Dead on arrival : a novel - Richtel, Matt (William Morrow, an imprint of HarperCollinsPublishers, 2017)
The bizarre deaths of everyone in a remote Colorado ski town thrusts world-class virologist Lyle Martin into a mystery involving a deadly syndrome that causes him to wonder if the world might be better left unsaved.